Preparation method of negative electrode of lithium ion battery
The negative electrode of lithium-ion battery was prepared by mixing and grinding self-assembled carbon nanotubes with carbonized polyimide films, supplemented with acetylene black and N-methylpyrrolidone solution using polyvinylidene fluoride as electrode binder, and the negative electrode of lithium-ion-ionized battery was solved In the prior art, the problem of insufficient capacity and cycle stability of lithium-ion batteries has achieved higher capacity and more stable cycle performance.
Patent Information
- Application Number
- CN202411797676.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-02-18
AI Technical Summary
During the preparation process of the negative electrode of existing lithium-ion batteries, improper carbon-based materials are easily affected by improper processing, which can easily affect the capacity and cycle stability of the lithium-ion batteries.
The active substance is prepared by mixing self-assembled carbon nanotubes and carbonized polyimide films, and secondary grinding is supplemented with acetylene black, and the N-methylpyrrolidone solution of polyvinylidene fluoride is combined as electrode adhesive. Lithium ion battery negative electrode.
It effectively improves the capacity and cycle stability of lithium-ion batteries, extends the service life, and builds a good conductive network, improving the electronic conduction efficiency.
Smart Images

Figure CN119480930A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium batteries, and in particular to a method for preparing a negative electrode of a lithium ion battery. Background Art
[0002] Lithium-ion battery is a secondary battery (rechargeable battery), mainly composed of positive electrode, separator, negative electrode, electrolyte and shell. It mainly relies on the movement of lithium ions between the positive electrode and the negative electrode to work. Among them, the negative electrode of lithium-ion battery is mainly composed of copper foil and carbon-based materials attached to the copper foil; however, carbon-based materials (including carbon nanotubes, carbon black, acetylene black, carbon fiber, conductive graphite, graphene, etc.) are of various types and different morphologies. When preparing the negative electrode of lithium-ion battery, if these carbon-based materials are not properly matched or processed, it is easy to affect the capacity and cycle stability of lithium-ion battery. Summary of the invention
[0003] The purpose of the present invention is to overcome the shortcomings of the prior art. The present invention provides a method for preparing a negative electrode for a lithium ion battery. The method comprises mixing and grinding self-assembled carbon nanotubes and carbonized polyimide films as active materials, and then preparing electrode powder with the aid of acetylene black. The N-methylpyrrolidone solution of polyvinylidene fluoride is used as an electrode binder. The prepared negative electrode for the lithium ion battery can effectively improve the capacity and cycle stability of the lithium ion battery.
[0004] The present invention provides a method for preparing a negative electrode of a lithium ion battery, comprising the following steps:
[0005] S1, taking 10 to 20 parts of self-assembled carbon nanotubes and 40 to 80 parts of carbonized polyimide films according to the first weight proportion, mixing and grinding to obtain an active substance;
[0006] The self-assembled carbon nanotubes are prepared by the following method: placing melamine in a first graphite mold of a tube furnace, and setting a product collector above the first graphite mold; heating to 1000-1400°C at a heating rate of 8-12°C / min under a vacuum environment, keeping the temperature for 20-40 minutes, and cooling naturally to obtain the self-assembled carbon nanotubes on the product collector;
[0007] S2, according to the second weight portion, taking 50-100 parts of the active material and 10-20 parts of acetylene black, mixing and grinding to obtain an electrode powder;
[0008] S3, dissolving 5 to 15 parts of polyvinylidene fluoride in 250 to 750 parts of N-methylpyrrolidone according to the third weight portion to obtain an electrode binder;
[0009] S4, taking 60 to 120 parts of the electrode powder and 340 to 680 parts of the electrode binder according to the fourth weight part and mixing them evenly to obtain an electrode slurry;
[0010] S5. Coating the electrode slurry on the surface of the copper foil, and obtaining a negative electrode of a lithium ion battery after drying.
[0011] Specifically, the following steps are included:
[0012] S11, taking 15 parts of self-assembled carbon nanotubes and 60 parts of carbonized polyimide films according to the first weight proportion, mixing and grinding to obtain an active substance;
[0013] The self-assembled carbon nanotubes are prepared by the following method: placing melamine in a first graphite mold of a tube furnace, and setting a product collector above the first graphite mold; heating to 1200°C at a heating rate of 10°C / min under a vacuum environment, keeping the temperature for 30 minutes, and cooling naturally to obtain self-assembled carbon nanotubes on the product collector;
[0014] S21, taking 75 parts of the active material and 15 parts of acetylene black according to the second weight portion, mixing and grinding to obtain an electrode powder;
[0015] S31, dissolving 10 parts of polyvinylidene fluoride in 500 parts of N-methylpyrrolidone according to the third weight portion to obtain an electrode binder;
[0016] S41, taking 90 parts of the electrode powder and 510 parts of the electrode binder according to the fourth weight part and mixing them evenly to obtain an electrode slurry;
[0017] S51, coating the electrode slurry on the surface of copper foil, and obtaining a negative electrode of a lithium ion battery after drying.
[0018] Specifically, in step S1, before heating the melamine, the following steps are performed:
[0019] The tube furnace is first evacuated, and then purged with argon gas, and the cycle is repeated at least three times.
[0020] Specifically, the carbonized polyimide film is prepared by the following method:
[0021] Preparing a precursor, dissolving a diamine monomer and a dianhydride monomer in a polar solvent, and reacting to obtain a polyamic acid solution; the molar ratio of the diamine monomer to the dianhydride monomer is 1:1;
[0022] Prepare a film, cast the polyamic acid solution on a glass sheet and dry it, and then obtain a polyimide film by a thermal imidization method;
[0023] Carbonization: placing the polyimide film in a second graphite mold of a tubular furnace, heating it to 800-1000° C. at a heating rate of 2-4° C. / min under a vacuum environment, and obtaining a carbonized polyimide film after natural cooling.
[0024] Specifically, the preparation of the precursor includes:
[0025] Adding a diamine monomer into a polar solvent and stirring at a speed of 300 to 350 r / min until the diamine monomer is completely dissolved to obtain a diamine solution;
[0026] Add dianhydride monomer to the diamine solution, and stir at a speed of 100-150 r / min for at least 6 hours to obtain a polyamic acid solution.
[0027] Specifically, the film preparation comprises:
[0028] placing the polyamic acid solution in a vacuum device to remove bubbles and obtain a degassed solution;
[0029] Casting the degassed solution on a glass sheet and coating it evenly to obtain a wet-attached film sheet;
[0030] The wet-attached film is placed in an environment of 80 to 100° C. and baked for at least 30 minutes to obtain a dry-attached film;
[0031] The dry-attached film is first placed in an environment of 240-260° C. and baked for 8-12 minutes, and then heated to 340-360° C. and baked for 8-12 minutes to obtain a polyimide film.
[0032] Specifically, before step S3, the process includes: drying the polyvinylidene fluoride in an environment of 70 to 100° C. for 1 to 5 minutes, and cooling the polyvinylidene fluoride to room temperature for standby use.
[0033] Specifically, in step S3, it includes: stirring the mixture of the polyvinylidene fluoride and the N-methylpyrrolidone at a rotation speed of 600-800 r / min until the polyvinylidene fluoride is completely dissolved.
[0034] Specifically, step S5 includes: placing the copper foil coated with the electrode slurry in a vacuum environment at 55 to 65° C. and drying for 10 to 20 hours.
[0035] Specifically, in step S5, the thickness of the copper foil is in the range of 4.5 to 8 μm, and the thickness of the electrode slurry coating is in the range of 90 to 120 μm.
[0036] Compared with the prior art, the present invention has the following beneficial effects:
[0037] In the preparation method of the negative electrode of the lithium ion battery of the present invention, the self-assembled carbon nanotubes are self-assembled from melamine through heat treatment, do not rely on any catalyst, and appear as black floccules on a macro scale, with high purity and high degree of graphitization; the self-assembled carbon nanotubes are mixed and ground with a carbonized polyimide film in a certain weight proportion to effectively form an active substance with a composite structure, and the active substance has good structural stability after being solidified on the copper foil, is not easy to break or expand, and is easy to embed and remove lithium ions, and can effectively improve the cycle stability and service life of the lithium ion battery; the active substance can also effectively construct a good conductive network, improve the electronic conduction efficiency, and thus improve the capacity of the lithium ion battery.
[0038] The electrode powder is made by secondary grinding with the aid of acetylene black. On the one hand, acetylene black has good dispersibility and can be evenly dispersed in the electrode powder to prevent the agglomeration of active substances. On the other hand, acetylene black has a high specific surface area and excellent conductivity, which can effectively increase the conductive contact points inside the negative electrode of the lithium-ion battery in the future, thereby further improving the transmission efficiency of electrons and increasing the capacity of the lithium-ion battery.
[0039] The N-methylpyrrolidone solution of polyvinylidene fluoride is used as an electrode binder, which has good fusion with the electrode powder. The prepared electrode slurry system is uniform and can be firmly attached to the surface of the copper foil, which is conducive to the formation of a negative electrode material layer with uniform composition and stable structure, and plays a positive role in improving the cycle stability and service life of lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0041] Figure 1 1 is a schematic diagram of a first process of a method for preparing a negative electrode of a lithium-ion battery in an embodiment of the present invention;
[0042] Figure 2 1 is a schematic diagram of a process for preparing a carbonized polyimide film according to an embodiment of the present invention;
[0043] Figure 3 1 is a second schematic flow chart of the method for preparing a negative electrode of a lithium ion battery in an embodiment of the present invention;
[0044] Figure 4 is a group of SEM images of the self-assembled carbon nanotubes of Example 1, wherein (a) and (b) are SEM images at different magnifications;
[0045] Figure 5 is a TEM image of a first single tube of the self-assembled carbon nanotube of Example 1 and a corresponding EDS element mapping image group;
[0046] Figure 6 is a set of TEM images of the self-assembled carbon nanotubes of Example 1, wherein (a) and (b) are TEM images at different magnifications;
[0047] Figure 7 TEM images of the second single tube of the self-assembled carbon nanotube of Example 1 and HRTEM images of the corresponding red frame area, wherein (c) is a TEM image and (d) is a HRTEM image;
[0048] Figure 8 TEM images of the third single tube of the self-assembled carbon nanotube of Example 1 and HRTEM images of the corresponding red frame area, wherein (e) is a TEM image and (f) is a HRTEM image;
[0049] Fig. 9 is the XPS overall spectrum of the self-assembled carbon nanotubes of Example 1;
[0050] Fig.10 is the C1s high-resolution spectrum of the self-assembled carbon nanotubes of Example 1;
[0051] Fig.11 is the N1s high-resolution spectrum of the self-assembled carbon nanotubes of Example 1;
[0052] Fig.12 is the XRD spectrum of the self-assembled carbon nanotubes of Example 1;
[0053] Fig.13 is a Raman spectrum of the self-assembled carbon nanotubes of Example 1;
[0054] Fig.14 1 is a cycle performance test diagram of Example 1 and Comparative Example 1;
[0055] Fig.15 It is a rate performance test diagram of Example 1 and Comparative Example 1. DETAILED DESCRIPTION
[0056] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0057] The present invention provides a method for preparing a negative electrode of a lithium ion battery. Figure 1 The first process schematic diagram of the method for preparing the negative electrode of a lithium ion battery in an embodiment of the present invention is shown, comprising the following steps:
[0058] S1, taking 10 to 20 parts of self-assembled carbon nanotubes and 40 to 80 parts of carbonized polyimide films according to the first weight proportion, mixing and grinding to obtain an active substance;
[0059] Optionally, 10 parts of self-assembled carbon nanotubes and 40 parts of carbonized polyimide films are mixed and ground, or 15 parts of self-assembled carbon nanotubes and 60 parts of carbonized polyimide films are mixed and ground, or 20 parts of self-assembled carbon nanotubes and 80 parts of carbonized polyimide films are mixed and ground; that is, the weight ratio of the self-assembled carbon nanotubes and the carbonized polyimide films is 1:4, which lays a foundation for the active substances with good composite structure formed by the mixed grinding of the self-assembled carbon nanotubes and the carbonized polyimide films.
[0060] In some specific embodiments, the self-assembled carbon nanotubes are prepared by the following method: melamine is placed in a first graphite mold of a tube furnace, and a product collector is arranged above the first graphite mold; in a vacuum environment, the temperature is increased to 1000-1400°C at a heating rate of 8-12°C / min, the temperature is kept for 20-40 minutes, and the self-assembled carbon nanotubes are obtained on the product collector; the method does not rely on any catalyst, and the melamine is self-assembled to generate carbon nanotubes by heat treatment, which are all black floccules in macroscopic view, the product is clean, there are no other by-products, and the degree of graphitization is high. Specifically, the diameter of the self-assembled carbon nanotubes ranges from 100 to 200 nm, the length of the self-assembled carbon nanotubes is much greater than 15 μm, the aspect ratio of the self-assembled carbon nanotubes is much greater than 100, the wall thickness of the self-assembled carbon nanotubes ranges from 3 to 5 nm, and the atomic percentage of C element in the self-assembled carbon nanotubes is greater than 90 at%.
[0061] Mixing and grinding self-assembled carbon nanotubes with carbonized polyimide films can effectively form a composite structure active material. After being solidified on copper foil, the active material has good structural stability, is not easy to break or expand, and is easy to embed and remove lithium ions, which can effectively improve the cycle stability and service life of lithium-ion batteries; the active material can also effectively construct a good conductive network, improve the efficiency of electronic conduction, and thus increase the capacity of lithium-ion batteries.
[0062] In some specific embodiments, the self-assembled carbon nanotubes and the carbonized polyimide film are placed in a mortar and ground clockwise or counterclockwise until the black floccules and film-like objects completely disappear and a uniform powder state is present. The clockwise or counterclockwise unidirectional grinding method is conducive to reducing the agglomeration of active substances; when the black floccules and film-like objects completely disappear, it is not suitable to continue to grind vigorously, otherwise it is easy to grind excessively, resulting in the destruction of the good composite structure of the active substance.
[0063] In some specific embodiments, before heating the melamine, the steps include:
[0064] The tube furnace is first evacuated, and then argon is used to purge the tube furnace. The operation is repeated at least three times to completely remove the air in the tube furnace, thereby preventing oxidation of melamine and preventing impurity gases from being mixed into the product to cause structural defects.
[0065] Figure 2 The schematic diagram of the process of preparing the carbonized polyimide film in the embodiment of the present invention is shown. The carbonized polyimide film is prepared by the following method:
[0066] S101, preparing a precursor, dissolving a diamine monomer and a dianhydride monomer in a polar solvent, and reacting to obtain a polyamic acid solution;
[0067] The molar ratio of the diamine monomer to the dianhydride monomer is 1:1, the diamine monomer is an aromatic diamine, such as 4,4'-diaminodiphenyl ether, 2,4-toluenediamine, etc.; the dianhydride monomer is an aromatic dianhydride, such as pyromellitic acid dianhydride, biphenyltetracarboxylic acid dianhydride, etc.; the polar solvent is one of dimethylformamide, dimethylacetamide, tetrahydrofuran / methanol mixed solution, and N-methylpyrrolidone, which is conducive to fully dissolving the diamine monomer and the dianhydride monomer, and providing a good solvent environment for the prepolymerization of the diamine monomer and the dianhydride monomer.
[0068] Specifically, a diamine monomer is first added to a polar solvent, and stirred at a speed of 300 to 350 r / min until the diamine monomer is completely dissolved to obtain a diamine solution; then a dianhydride monomer is added to the diamine solution, and stirred at a speed of 100 to 150 r / min for at least 6 hours to obtain a polyamic acid solution, ensuring that the diamine monomer and the dianhydride monomer are fully reacted to generate polyamic acid.
[0069] Preferably, 4,4'-diaminodiphenyl ether is first added to dimethylacetamide, and stirred at a speed of 320 r / min until 4,4'-diaminodiphenyl ether is completely dissolved to obtain a diamine solution; then, pyromellitic dianhydride is gradually added to the diamine solution, and stirred at a speed of 120 r / min for 6 hours to obtain a polyamic acid solution, which is beneficial for the subsequently obtained polyimide film to obtain a high degree of graphitization during carbonization.
[0070] S102, preparing a film, casting the polyamic acid solution on a glass sheet and drying it, and then obtaining a polyimide film by a thermal imidization method;
[0071] Specifically, the polyamic acid solution is first placed in a vacuum device to remove bubbles to obtain a degassed solution, thereby avoiding the presence of bubbles that may cause defects in the subsequently formed film; the degassed solution is then cast on a glass sheet and evenly coated to obtain a wet-attached film, which is beneficial to improving the thickness uniformity of subsequent film forming; the wet-attached film is then placed in an environment of 80 to 100° C. and baked for at least 30 minutes to obtain a dry-attached film, the solvent is removed, and the polyamic acid is solidified on the glass sheet to form a film, laying the foundation for subsequent thermal imidization; the dry-attached film is then placed in an environment of 240 to 260° C. and baked for 8 to 12 minutes, and finally the temperature is raised to 340 to 360° C. and baked for 8 to 12 minutes to obtain a polyimide film, thereby ensuring "complete" imidization.
[0072] Preferably, the polyamic acid solution is placed in a vacuum device to remove bubbles to obtain a degassed solution; the degassed solution is cast on a high-temperature resistant glass sheet and evenly coated with a coating machine to obtain a wet-attached film; the wet-attached film is placed in a 90°C oven and baked for 30 minutes to obtain a dry-attached film; the dry-attached film is placed in a 250°C oven and baked for 10 minutes, and then heated to 350°C and baked for 10 minutes to obtain a polyimide film. This not only achieves "complete" imidization, but also improves the mechanical properties of the obtained polyimide film, laying a good foundation for subsequent carbonization.
[0073] S103, carbonization, placing the polyimide film in a second graphite mold of a tubular furnace, heating to 800-1000° C. at a heating rate of 2-4° C. / min under a vacuum environment, and obtaining a carbonized polyimide film after natural cooling;
[0074] A heating rate of 2 to 4°C / min is conducive to uniform heating of the polyimide film and avoids curling of the polyimide film; heating to 800 to 1000°C can make the structure of the film grow from an amorphous anisotropic state to a hexagonal carbon layer structure. The carbonized polyimide film prepared by this method is in the form of a complete film, brittle, highly graphitized, and has good electrical conductivity. When mixed and ground with self-assembled carbon nanotubes, it can effectively form an active substance with a composite structure.
[0075] S2, according to the second weight portion, taking 50-100 parts of the active material and 10-20 parts of acetylene black, mixing and grinding to obtain an electrode powder;
[0076] The electrode powder is made by secondary grinding with the aid of acetylene black. On the one hand, acetylene black has good dispersibility and can be evenly dispersed in the electrode powder to prevent the agglomeration of active substances. On the other hand, acetylene black has a high specific surface area and excellent conductivity, which can effectively increase the conductive contact points inside the negative electrode of the lithium-ion battery in the future, thereby further improving the transmission efficiency of electrons and increasing the capacity of the lithium-ion battery.
[0077] Optionally, 50 parts of the active substance and 10 parts of acetylene black are mixed and ground, or 75 parts of the active substance and 15 parts of acetylene black are mixed and ground, or 100 parts of the active substance and 20 parts of acetylene black are mixed and ground; that is, the weight ratio of the active substance to acetylene black is 5:1, ensuring that acetylene black can fully exert its effect, while avoiding excessive acetylene black that weakens the effect of the active substance.
[0078] Specifically, the active substance and acetylene black are placed in a mortar and ground clockwise or counterclockwise until they are evenly mixed; the grinding direction is preferably consistent with the direction when the active substance is ground, and the grinding action is gentle, which is beneficial to protecting the active substance.
[0079] S3, dissolving 5 to 15 parts of polyvinylidene fluoride in 250 to 750 parts of N-methylpyrrolidone according to the third weight portion to obtain an electrode binder;
[0080] Polyvinylidene fluoride, abbreviated as PVDF, is a highly non-reactive thermoplastic fluorinated polymer; N-methylpyrrolidone, abbreviated as NMP, is an organic solvent with high solvency and low toxicity; NMP can interact with PVDF molecules through intermolecular forces, destroying the crystal structure of PVDF molecules and making it an amorphous state soluble in NMP.
[0081] The N-methylpyrrolidone solution of polyvinylidene fluoride is used as an electrode binder, which has good fusion with the electrode powder. The prepared electrode slurry system is uniform and can be firmly attached to the surface of the copper foil, which is conducive to the formation of a negative electrode material layer with uniform composition and stable structure, and plays a positive role in improving the cycle stability and service life of lithium-ion batteries.
[0082] Optionally, 5 parts of polyvinylidene fluoride are dissolved in 250 parts of N-methylpyrrolidone, or 10 parts of polyvinylidene fluoride are dissolved in 500 parts of N-methylpyrrolidone, or 15 parts of polyvinylidene fluoride are dissolved in 750 parts of N-methylpyrrolidone; that is, the weight ratio of polyvinylidene fluoride to N-methylpyrrolidone is 1:50, ensuring that the obtained electrode adhesive is compatible with the electrode powder.
[0083] In some specific embodiments, before step S3, the step includes: drying the polyvinylidene fluoride in an environment of 70-100°C for 1-5 minutes, and cooling to room temperature for standby use, so as to remove moisture from the polyvinylidene fluoride and improve the quality of the electrode adhesive. Preferably, drying the polyvinylidene fluoride in an infrared drying oven at 80-90°C for 3 minutes is beneficial to avoid discoloration of the polyvinylidene fluoride.
[0084] In some specific embodiments, the mixture of the polyvinylidene fluoride and the N-methylpyrrolidone is stirred at a speed of 600 to 800 r / min until the polyvinylidene fluoride is completely dissolved. Such a relatively high rotation speed is conducive to quickly dispersing the polyvinylidene fluoride into the N-methylpyrrolidone; at the same time, the rotation speed is not higher than 800 r / min, which can avoid too many bubbles from being mixed into the solution during the stirring process. Preferably, the mixture of the polyvinylidene fluoride and the N-methylpyrrolidone is stirred at a speed of 700 r / min, and the polyvinylidene fluoride can be completely dispersed in about 1 hour, and the obtained electrode adhesive has few bubbles.
[0085] S4, taking 60 to 120 parts of the electrode powder and 340 to 680 parts of the electrode binder according to the fourth weight part and mixing them evenly to obtain an electrode slurry;
[0086] Optionally, 60 parts of the electrode powder and 340 parts of the electrode adhesive are mixed evenly, or 90 parts of the electrode powder and 510 parts of the electrode adhesive are mixed evenly, or 120 parts of the electrode powder and 680 parts of the electrode adhesive are mixed evenly; that is, the weight ratio of the electrode powder to the electrode adhesive is 3:17. The electrode powder and the electrode adhesive in this ratio have good fusion properties, and the prepared electrode slurry system is uniform and can be firmly attached to the surface of the copper foil, which is conducive to forming a negative electrode material layer with uniform composition and stable structure, and has a positive effect on improving the cycle stability and service life of lithium-ion batteries.
[0087] In some specific embodiments, the electrode powder and the electrode binder are stirred for at least 2 hours to obtain an electrode slurry with a viscosity ranging from 140 to 160 centipoise, which is convenient for subsequent coating on a copper foil.
[0088] Specifically, a magnetic stirrer is used to stir the electrode powder and the electrode binder. The magnetic stirring process is relatively gentle and is conducive to protecting the good composite structure of the active material.
[0089] S5, coating the electrode slurry on the surface of the copper foil, and obtaining a negative electrode of a lithium ion battery after drying;
[0090] Specifically, before coating the electrode slurry, use alcohol and absorbent cotton to clean the surface of the copper foil to avoid dust that affects the quality of the negative electrode of the lithium-ion battery.
[0091] Furthermore, the copper foil coated with the electrode slurry is placed in a vacuum environment at 55 to 65° C. and dried for 10 to 20 hours, so that a large amount of NMP in the electrode slurry can be removed, while avoiding excessive drying of the electrode slurry and oxidation of the copper foil. Preferably, the copper foil coated with the electrode slurry is placed in a vacuum environment at 60° C. and dried for 14 hours, and the obtained lithium ion battery negative electrode is of high quality and not easy to fall off.
[0092] In some specific embodiments, the thickness of the copper foil is in the range of 4.5 to 8 μm, and the thickness of the electrode slurry coating is in the range of 90 to 120 μm. After drying, no tableting is required. The active material and acetylene black have formed a good conductive network. Without tableting, sufficient ion channels can be retained to facilitate the movement of lithium ions. Preferably, the thickness of the copper foil is 6 μm, and the thickness of the electrode slurry coating is 105 μm, which is cost-effective.
[0093] Preferably, Figure 3 The second schematic flow chart of the method for preparing a negative electrode of a lithium ion battery in an embodiment of the present invention is shown. The method for preparing a negative electrode of a lithium ion battery in the present invention comprises the following steps:
[0094] S11, taking 15 parts of self-assembled carbon nanotubes and 60 parts of carbonized polyimide films according to the first weight proportion, mixing and grinding to obtain an active substance;
[0095] The self-assembled carbon nanotubes are prepared by the following method: placing melamine in a first graphite mold of a tube furnace, and setting a product collector above the first graphite mold; heating to 1200°C at a heating rate of 10°C / min under a vacuum environment, keeping the temperature for 30 minutes, and cooling naturally to obtain self-assembled carbon nanotubes on the product collector;
[0096] S21, taking 75 parts of the active material and 15 parts of acetylene black according to the second weight portion, mixing and grinding to obtain an electrode powder;
[0097] S31, dissolving 10 parts of polyvinylidene fluoride in 500 parts of N-methylpyrrolidone according to the third weight portion to obtain an electrode binder;
[0098] S41, taking 90 parts of the electrode powder and 510 parts of the electrode binder according to the fourth weight part and mixing them evenly to obtain an electrode slurry;
[0099] S51, coating the electrode slurry on the surface of copper foil, and obtaining a negative electrode of a lithium ion battery after drying.
[0100] In the preparation method of the negative electrode of the lithium ion battery of the present invention, the self-assembled carbon nanotubes are self-assembled from melamine by heat treatment, do not rely on any catalyst, and are all black floccules in macroscopic view, with high purity and high degree of graphitization; specifically, the diameter range of the self-assembled carbon nanotubes is 100-200nm, the length is much greater than 15μm, the aspect ratio is much greater than 100, the tube wall thickness range is 3-5nm, and the atomic percentage of the C element is greater than 90at%; the self-assembled carbon nanotubes are mixed and ground with the carbonized polyimide film according to a certain weight fraction to effectively form an active substance with a composite structure, and the active substance has good structural stability after being solidified on the copper foil, is not easy to break or expand, and is easy to embed and remove lithium ions, and can effectively improve the cycle stability and service life of the lithium ion battery; the active substance can also effectively construct a good conductive network, improve the electronic conduction efficiency, and thus improve the capacity of the lithium ion battery.
[0101] The electrode powder is made by secondary grinding with the aid of acetylene black. On the one hand, acetylene black has good dispersibility and can be evenly dispersed in the electrode powder to prevent the agglomeration of active substances. On the other hand, acetylene black has a high specific surface area and excellent conductivity, which can effectively increase the conductive contact points inside the negative electrode of the lithium-ion battery in the future, thereby further improving the transmission efficiency of electrons and increasing the capacity of the lithium-ion battery.
[0102] The N-methylpyrrolidone solution of polyvinylidene fluoride is used as an electrode binder, which has good fusion with the electrode powder. The prepared electrode slurry system is uniform and can be firmly attached to the surface of the copper foil, which is conducive to the formation of a negative electrode material layer with uniform composition and stable structure, and plays a positive role in improving the cycle stability and service life of lithium-ion batteries.
[0103] Example 1
[0104] (1) 15 mg of self-assembled carbon nanotubes and 60 mg of carbonized polyimide film were mixed and ground to obtain an active substance;
[0105] Wherein, the self-assembled carbon nanotubes are prepared by the following method:
[0106] First, melamine is simply ground in a quartz mortar; then, melamine is placed in a first graphite mold of a tubular furnace, and a product collector is set above the first graphite mold; before heating, the tubular furnace is first evacuated, and then high-purity argon is used to purge the tubular furnace, the operation is repeated three times, and finally the vacuum environment is maintained; under the vacuum environment, the temperature is increased to 1200°C at a heating rate of 10°C / min, the temperature is kept for 30 minutes, and the mixture is naturally cooled to obtain self-assembled carbon nanotubes on the product collector.
[0107] Wherein, the carbonized polyimide film is prepared by the following method:
[0108] First, a precursor is prepared: 4,4'-diaminodiphenyl ether is added to dimethylacetamide, and stirred at a speed of 320 r / min until 4,4'-diaminodiphenyl ether is completely dissolved to obtain a diamine solution; then, pyromellitic acid dianhydride is gradually added to the diamine solution, and stirred at a speed of 120 r / min for 6 hours to obtain a polyamic acid solution; the molar ratio of 4,4'-diaminodiphenyl ether to pyromellitic acid dianhydride is 1:1;
[0109] Then, a film is prepared: the polyamic acid solution is placed in a vacuum device to remove bubbles to obtain a degassed solution; the degassed solution is cast on a high-temperature resistant glass sheet and evenly coated with a coating machine to obtain a wet-attached film sheet; the wet-attached film sheet is placed in an oven at 90°C and baked for 30 minutes to obtain a dry-attached film sheet; the dry-attached film sheet is placed in an oven at 250°C and baked for 10 minutes, and then the temperature is raised to 350°C and baked for 10 minutes to obtain a polyimide film;
[0110] Finally, carbonization: the polyimide film is placed in a second graphite mold of a tubular furnace, and heated from room temperature to 800°C at a heating rate of 2°C / min under a vacuum environment, and a carbonized polyimide film is obtained after natural cooling.
[0111] (2) 75 mg of active material and 15 mg of acetylene black were mixed and ground in an agate mortar to obtain electrode powder;
[0112] (3) 10 mg of PVDF was placed in a weighing bottle and dried in an infrared drying oven at 85°C for 3 min. After cooling to room temperature, 500 mg of NMP was added to the weighing bottle and stirred at 700 r / min for 1 h to completely dissolve the PVDF to obtain an electrode adhesive.
[0113] (4) Add 90 mg of electrode powder into a weighing bottle, mix with 510 mg of electrode binder, and stir for 2 h to obtain electrode slurry;
[0114] (5) The electrode slurry is coated on a copper foil and dried in a vacuum environment at 60° C. for 14 h to obtain a negative electrode for a lithium-ion battery.
[0115] Comparative Example 1
[0116] 75 mg of the carbonized polyimide film was ground to obtain an active material, and the rest was the same as in Example 1 to prepare a negative electrode for a lithium ion battery.
[0117] Microscopic morphology of self-assembled carbon nanotubes in Example 1
[0118] Using industrial raw material melamine powder as the carbon source and directly passing through a tubular furnace for heat treatment, the prepared self-assembled carbon nanotubes all appear as black flocs on a macro scale. The product is clean and has no other by-products, and no post-processing processes such as purification are required.
[0119] Figure 4 The SEM image group of the self-assembled carbon nanotubes of Example 1 is shown, wherein (a) and (b) are SEM images at different magnifications. All the self-assembled carbon nanotubes are uniform and dense, with consistent structures. The tubular structures mainly present a slight bamboo-like shape, and the surface of the tube wall is smooth. The radial dimensions of the tubes are not much different, and the tube diameters are all in the range of 100 to 200 nm. According to statistics, the tube diameters basically present a normal distribution, and the average diameter is about 150 nm. The axial dimensions of all the self-assembled carbon nanotubes are in the micron range, and it is difficult to observe the end structure of the tube. The tube lengths are all much greater than 15 um, and the aspect ratio of the tubes is much greater than 100.
[0120] Figure 5 The TEM image of the first single tube of the self-assembled carbon nanotube of Example 1 and the corresponding EDS element mapping image group are shown. It can be clearly seen that the C element is densely and evenly distributed along the first single tube, and the distribution of the N and O elements is sharply reduced compared to the C element, indicating that the N element content in the first single tube is extremely small, and the response of the O element mainly comes from the adsorbed O; obviously, the elemental composition of the first single tube is mainly C element, and according to analysis, its relative atomic mass fraction is as high as 98.7at%.
[0121] Figure 6 The TEM images of the self-assembled carbon nanotubes of Example 1 are shown, where (a) and (b) are TEM images at different magnifications; the self-assembled carbon nanotubes present a periodic spacer morphology, a typical bamboo node morphology, and are obvious hollow tubes, with the axial length of a single bamboo node being about 100 to 200 nm. Since a certain angle is formed between adjacent bamboo nodes, the tube is prone to bending and winding during the axial growth process as the length of the tube increases, as shown in FIG. Figure 4 In addition, since the axial size of the growing self-assembled carbon nanotubes is much larger than the radial size, it is difficult to Figure 4 The end structure of the tube can only be observed in Figure 6 In b, the ends of very few tubes are observed. The ends of the tubes are obviously open, and it can be clearly seen that the tubes are hollow. The tube walls are thin relative to the overall size of the tubes. Therefore, the inner diameter and outer diameter of the tube structure are not distinguished, that is, the diameter of the opening is considered to be equivalent to the tube diameter.
[0122] Figure 7The TEM image of the second single tube of the self-assembled carbon nanotube of Example 1 and the HRTEM image of the corresponding red frame area are shown, wherein (c) is a TEM image and (d) is a HRTEM image; Figure 8 The TEM image of the third single tube of the self-assembled carbon nanotube of Example 1 and the HRTEM image of the corresponding red frame area are shown, wherein (e) is a TEM image and (f) is a HRTEM image. Figure 7 c and Figure 8 The red frame areas marked in e are the tube wall positions and the spacer layers inside the tube of the periodic bamboo-shaped tube structure, which are characterized by high-resolution transmission electron microscopy (HRTEM). Figure 7 d and Figure 8 f. Both the tube wall and the spacer layer inside the tube show high crystallinity, and the interlayer spacing of the crystals is 0.34nm, which is consistent with the interlayer spacing of the (002) crystal plane of existing graphite. The thickness of the tube wall is about 3-5nm, and it is composed of about 8-12 layers of graphene. It can be seen that the curvature of some graphene layers in both the tube wall and the spacer layer inside the tube has changed, especially the outermost graphene layer is prone to structural defects, resulting in bending of the tube microstructure. This may come from the structural defects caused by nitrogen doping, or it may be due to slight changes in the growth conditions of carbon nanotubes during the preparation process, such as fluctuations in gas flow or temperature, which leads to uneven tube diameters along the growth direction of the tube, which is prone to bending and winding of the tube, which is related to the Figure 4 The microscopic morphology observed in the experiment remains consistent.
[0123] Characterization of self-assembled carbon nanotubes
[0124] Fig. 9 The XPS total spectrum of the self-assembled carbon nanotubes of Example 1 is shown. The XPS total spectrum mainly shows a strong peak around 284eV, corresponding to the peak of C1s, while the detected N and O element signals are relatively weak. The peak near 401eV corresponds to the peak of N1s, and the peak near 532eV corresponds to the peak of O1s, indicating that the main element composition in the product is C element, and the relative atomic concentrations of N and O elements are extremely low, close to the detection limit of the instrument, wherein the O element may come from O adsorbed in the air, or the self-assembled carbon nanotubes are easily oxidized in the air to form surface oxides; according to test analysis, the atomic percentage of C element in the self-assembled carbon nanotubes is as high as 98.11%, which is consistent with the previous EDS data analysis. The self-assembled carbon nanotubes are mainly C elements, while the N element accounts for a very small proportion.
[0125] Fig.10The C1s high-resolution spectrum of the self-assembled carbon nanotubes of Example 1 is shown. The C1s peak of the self-assembled carbon nanotubes is basically an asymmetric single peak, with a peak position near 284eV, corresponding to the conjugated bond C=C formed by sp2 hybridized carbon atoms in the carbon product. The C1s symmetric loss peak fitted at 290.05eV mainly corresponds to the π-π* interaction between different carbon components or different graphene layers in the self-assembled carbon nanotubes, indicating that the self-assembled carbon nanotubes have a high degree of carbonization and have a certain graphite structure.
[0126] Fig.11 The N1s high-resolution spectrum of the self-assembled carbon nanotubes of Example 1 is shown. N exists in the self-assembled carbon nanotubes in the form of heteroatom doping. The nitrogen peaks of 398.19eV and 400.61eV fitted in the high-resolution N1s spectrum correspond to pyridine and graphitic nitrogen, respectively. Pyrrolic nitrogen is unstable at temperatures above 850° C. Since the raw material does not contain O element, the O element comes from O adsorbed in the air or a small amount of oxidation of the self-assembled carbon nanotubes.
[0127] Self-assembled carbon nanotubes are mainly composed of C elements, and carbon atoms mainly exist in sp2 hybridized form. Most of the N elements are pyrolyzed into small molecule overflow systems during the annealing process, and only a very small amount of N elements are doped in the graphene lattice of the carbon products in the form of pyridine and graphitic nitrogen. This shows that as the carbonization temperature increases, the product simultaneously achieves orderly rearrangement of C atoms in the process of losing N, forming a multi-layer graphene structure, which further self-assembles and curls from the sheet structure to form a tubular product.
[0128] Fig.12 The XRD spectrum of the self-assembled carbon nanotubes of Example 1 is shown. The collected self-assembled carbon nanotubes show an obvious sharp diffraction peak at 2θ=26.36°, which corresponds to the (002) crystal plane of lamellar graphite by comparison with the standard spectrum of graphite (PDF#00-001-0640), and has a slight displacement relative to the graphite peak position of single-walled carbon nanotubes (~26.5°). It may be due to the peak position shifting to the left due to the number of carbon nanotube layers, and the (002) diffraction peak presents an asymmetric peak shape due to the curvature of the tube structure and the uneven tube diameter. In addition, the weaker diffraction peak near 42.8° corresponds to the (100) crystal plane of graphite. Apart from this, there are no other diffraction peaks, which indicates that the synthesized self-assembled carbon nanotubes are pure and not contaminated by the catalyst, and the characteristic diffraction peak of graphite is narrow, indicating that the product has a high degree of graphitization and few lattice structure defects; further, through the Bragg equation calculation, it can be obtained that the graphite crystal interlayer spacing (d002) in the self-assembled carbon nanotubes is about 0.33783nm, and then it is substituted into the Mering-Maire formula for calculation, and the degree of graphitization of the carbon product is calculated to be 76.34%.
[0129] For self-assembled carbon nanotubes in the range of 500 to 3500 cm -1 Raman spectroscopy analysis is performed in the frequency range. Fig.13 The Raman spectrum of the self-assembled carbon nanotubes of Example 1 is shown. The self-assembled carbon nanotubes have the Raman spectra at 1350, 1580 and 2700 cm -1 There are three characteristic peaks near the position, corresponding to the D peak, G peak and G′ peak of graphene. -1 The G peak at , which is caused by the in-plane stretching vibration between sp2 hybridized carbon atoms, corresponds to the vibration of E2g optical phonon in the center of the Brillouin zone. The sharp G peak indicates that the self-assembled carbon nanotubes have a regular graphene structure and a high degree of graphitization.
[0130] At ~1350cm -1 The characteristic peak at , usually called D peak, is caused by the radial breathing mode of the symmetric stretching vibration of the sp2 carbon atoms in the aromatic ring, corresponding to the A1g phonon mode of the K point in the Brillouin zone. This peak is very sensitive to structural defects caused by element doping and surface modification, and is used to characterize crystal structural defects or edges in graphene samples.
[0131] Therefore, the ratio of peak D to peak G is D / I G It can be used to characterize the degree of defects in the sidewalls of synthesized self-assembled carbon nanotubes. The larger the ratio, the lower the order of carbon atoms in the material and the more lattice defects. Fig.13 From the data, it can be seen that the I D / I G The value is as low as 0.49, and the structural defects mainly come from the crystal structure defects caused by N atom doping and the increase in the number of carbon nanotube layers.
[0132] Appeared at 2700cm -1 The characteristic peak near the D peak, usually called the 2D peak or G' peak, is the double frequency peak of the D peak. It originates from the double resonance transition of two phonons with opposite momentum in the carbon atoms. This peak can effectively reflect the number of graphene layers. As the number of layers increases, the intensity of the G' peak decreases, and the half-peak width of the G' peak gradually increases and shifts to higher wave numbers. The intensity ratio of the G' band to the G band (I G′ / I G ) has been used as an effective method to characterize the thickness of graphene or carbon nanotubes. G′ / I G The value indicates that the thickness of the formed carbon nanotubes is relatively large, and the I G′ / I GThe value is about 0.5. Compared with the single-layer graphene spectrum, the 2D peak is broader, indicating that the prepared self-assembled carbon nanotubes are composed of multi-layer graphene. Importantly, these Raman results on thickness are consistent with high-resolution transmission electron microscopy (HR-TEM) images, and the synthesized self-assembled carbon nanotubes have about 8 to 12 layers.
[0133] Electrochemical performance test
[0134] The negative electrode of the lithium ion battery obtained in Example 1 was cut into a first pole piece with a diameter of 12 mm, and aluminum foil was used as the counter electrode, polypropylene was used as the diaphragm, and LiPF6 / EC / DMC / EMC was used as the electrolyte, and the first CR2023 button battery was assembled in a glove box with an Ar atmosphere; the negative electrode of the lithium ion battery obtained in Comparative Example 1 was cut into a second pole piece with a diameter of 12 mm, and aluminum foil was used as the counter electrode, polypropylene was used as the diaphragm, and LiPF6 / EC / DMC / EMC was used as the electrolyte, and the second CR2023 button battery was assembled in a glove box with an Ar atmosphere.
[0135] The first CR2023 button cell and the second CR2023 button cell were tested for cycle performance and rate capacity: the cycle performance of the lithium-ion button cell was tested by charging and discharging 300 times at 0.1C in the voltage range of 0.01 to 3V; the rate performance of the lithium-ion button cell was evaluated by charging and discharging continuously for 5 cycles at a current density ranging from 0.1 to 4C.
[0136] The electrochemical performance of self-assembled carbon nanotubes was studied by assembling lithium-ion button cells. Fig.14 The cycle performance test diagrams of Example 1 and Comparative Example 1 are shown, and the current density used for the test is 0.1C. Compared with the second pole piece of Comparative Example 1, since the first pole piece of Example 1 adds self-assembled carbon nanotubes as active materials, the reversible specific capacity of the first pole piece of Example 1 is increased by about 50mAh / g, and after 250 long cycles, the capacity of the first pole piece of Example 1 is steadily increased to 309mAh / g, while the capacity of the second pole piece of Comparative Example 1 is 186mAh / g, that is, the capacity of the first pole piece of Example 1 is increased more, reaching 123mAh / g, and its coulombic efficiency is almost always maintained at about 100% in 250 cycles. Therefore, adding self-assembled carbon nanotubes as active materials in the carbonized polyimide film matrix is not only beneficial to improving the capacity of the lithium-ion battery, but also its cycle stability is greatly improved, which is beneficial to extending the service life of the lithium-ion battery.
[0137] Fig.15The rate performance test diagrams of Example 1 and Comparative Example 1 are shown. It can be found that compared with the second pole piece of Comparative Example 1, the first pole piece of Example 1 exhibits higher specific capacity and better cycle performance at different current densities; specifically, for the first pole piece of Example 1, its initial discharge specific capacity is as high as 890mAh / g, and the discharge specific capacities at 0.1C, 0.2C, 0.5C, 1C, 2C, and 4C are 300mAh / g, 185mAh / g, 137mAh / g, 114mAh / g, 87mAh / g, and 60mAh / g, respectively. When the current density is 0.5C, 1C, and 2C again, the discharge specific capacities are 177mAh / g, 156mAh / g, and 112mAh / g, respectively, all exceeding the initial capacity, indicating that the crystal structure of the first pole piece of Example 1 will not be destroyed during high-rate charge and discharge, and it not only has good reversibility, but also has post-activation characteristics.
[0138] In general, compared with the second electrode of comparative example 1, the first electrode of example 1 not only has a greatly improved specific capacity, but also has a significantly increased cycle stability, showing more superior electrochemical performance.
[0139] Summarize
[0140] Under the condition of no catalyst and no template, the melamine raw material is directly heat-treated in one step to synthesize self-assembled carbon nanotubes with bamboo-like hollow structure, and the tube diameter is uniform, ranging from 100 to 200nm, and the length of the tube is in the micrometer range, with an ultra-high aspect ratio, which is a typical one-dimensional quantum material; further, through TEM images, it is found that the wall thickness of the synthesized hollow morphology self-assembled carbon nanotubes is about 3 to 5nm, and it is composed of 8 to 12 layers of curled graphene; further XPS, XRD, and Raman characterization of the self-assembled carbon nanotubes are confirmed that the self-assembled carbon nanotubes synthesized with melamine as the carbon source have a high degree of graphitization, and the atomic percentage of C element is as high as 98.11at%, which is completely different from the CN ratio in g-C3N4 nanotubes. There is only a very small amount of N element in the self-assembled carbon nanotubes, which is doped in the tube structure in the form of graphite N and pyridine N, resulting in certain structural defects, but the overall graphite crystal structure is relatively complete, and the intensity ratio of D peak to G peak in the Raman spectrum (I D / I G ) is as low as 0.49, with a good graphite structure; further, the synthesized self-assembled carbon nanotubes are applied to lithium-ion batteries, and the prepared self-assembled carbon nanotube / carbonized polyimide film composite lithium-ion battery negative electrode shows better capacity, rate and cycle stability.
[0141] The above is a detailed introduction to the preparation method of a lithium-ion battery negative electrode provided by an embodiment of the present invention. Specific examples are used herein to illustrate the principle and implementation method of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea. At the same time, for a person skilled in the art, according to the idea of the present invention, there will be changes in the specific implementation method and application scope. In summary, the content of this specification should not be understood as a limitation on the present invention.
Claims
1. A method for preparing a negative electrode of a lithium ion battery, characterized in that: The following steps are involved: S1, taking 10 to 20 parts of self-assembled carbon nanotubes and 40 to 80 parts of carbonized polyimide films according to the first weight proportion, mixing and grinding to obtain an active substance; The self-assembled carbon nanotubes are prepared by the following method: placing melamine in a first graphite mold of a tube furnace, and setting a product collector above the first graphite mold; heating to 1000-1400°C at a heating rate of 8-12°C / min under a vacuum environment, keeping the temperature for 20-40 minutes, and cooling naturally to obtain the self-assembled carbon nanotubes on the product collector; S2, according to the second weight portion, taking 50-100 parts of the active material and 10-20 parts of acetylene black, mixing and grinding to obtain an electrode powder; S3, dissolving 5 to 15 parts of polyvinylidene fluoride in 250 to 750 parts of N-methylpyrrolidone according to the third weight portion to obtain an electrode binder; S4, taking 60 to 120 parts of the electrode powder and 340 to 680 parts of the electrode binder according to the fourth weight part and mixing them evenly to obtain an electrode slurry; S5. Coating the electrode slurry on the surface of the copper foil, and obtaining a negative electrode of a lithium ion battery after drying.
2. The method for preparing a negative electrode for a lithium ion battery according to claim 1, wherein: The following steps are involved: S11, taking 15 parts of self-assembled carbon nanotubes and 60 parts of carbonized polyimide films according to the first weight proportion, mixing and grinding to obtain an active substance; The self-assembled carbon nanotubes are prepared by the following method: placing melamine in a first graphite mold of a tube furnace, and setting a product collector above the first graphite mold; heating to 1200°C at a heating rate of 10°C / min under a vacuum environment, keeping the temperature for 30 minutes, and cooling naturally to obtain self-assembled carbon nanotubes on the product collector; S21, taking 75 parts of the active material and 15 parts of acetylene black according to the second weight portion, mixing and grinding to obtain an electrode powder; S31, dissolving 10 parts of polyvinylidene fluoride in 500 parts of N-methylpyrrolidone according to the third weight portion to obtain an electrode binder; S41, taking 90 parts of the electrode powder and 510 parts of the electrode binder according to the fourth weight part and mixing them evenly to obtain an electrode slurry; S51, coating the electrode slurry on the surface of copper foil, and obtaining a negative electrode of a lithium ion battery after drying.
3. The method for preparing a negative electrode for a lithium ion battery according to claim 1, characterized in that: In step S1, before heating the melamine, the following steps are performed: The tube furnace is first evacuated, and then purged with argon gas, and the cycle is repeated at least three times.
4. The method for preparing a negative electrode for a lithium ion battery according to claim 1, wherein: The carbonized polyimide film is prepared by the following method: Preparing a precursor, dissolving a diamine monomer and a dianhydride monomer in a polar solvent, and reacting to obtain a polyamic acid solution; the molar ratio of the diamine monomer to the dianhydride monomer is 1:1; Prepare a film, cast the polyamic acid solution on a glass sheet and dry it, and then obtain a polyimide film by a thermal imidization method; Carbonization: placing the polyimide film in a second graphite mold of a tubular furnace, heating it to 800-1000° C. at a heating rate of 2-4° C. / min under a vacuum environment, and obtaining a carbonized polyimide film after natural cooling.
5. The method for preparing a negative electrode for a lithium ion battery according to claim 4, characterized in that: The preparation of the precursor comprises: Adding a diamine monomer into a polar solvent and stirring at a speed of 300 to 350 r / min until the diamine monomer is completely dissolved to obtain a diamine solution; Add dianhydride monomer to the diamine solution, and stir at a speed of 100-150 r / min for at least 6 hours to obtain a polyamic acid solution.
6. The method for preparing a negative electrode for a lithium ion battery according to claim 4, characterized in that: The film preparation comprises: placing the polyamic acid solution in a vacuum device to remove bubbles and obtain a degassed solution; Casting the degassed solution on a glass sheet and coating it evenly to obtain a wet-attached film sheet; The wet-attached film is placed in an environment of 80 to 100° C. and baked for at least 30 minutes to obtain a dry-attached film; The dry-attached film is first placed in an environment of 240-260° C. and baked for 8-12 minutes, and then heated to 340-360° C. and baked for 8-12 minutes to obtain a polyimide film.
7. The method for preparing a negative electrode for a lithium ion battery according to claim 1, characterized in that: Before step S3, the method includes: placing the polyvinylidene fluoride in an environment of 70 to 100° C. for drying for 1 to 5 minutes, and cooling the polyvinylidene fluoride to room temperature for standby use.
8. The method for preparing a negative electrode for a lithium ion battery according to claim 1, characterized in that: In step S3, it includes: stirring the mixture of the polyvinylidene fluoride and the N-methylpyrrolidone at a rotation speed of 600 to 800 r / min until the polyvinylidene fluoride is completely dissolved.
9. The method for preparing a negative electrode for a lithium ion battery according to claim 1, characterized in that: Step S5 includes: placing the copper foil coated with the electrode slurry in a vacuum environment at 55 to 65° C. and drying for 10 to 20 hours.
10. The method for preparing a negative electrode for a lithium ion battery according to claim 1, characterized in that: In step S5, the thickness of the copper foil is in the range of 4.5 to 8 μm, and the thickness of the electrode slurry coating is in the range of 90 to 120 μm.